Testosterone therapy in diabetes and pre‐diabetes. (29th December 2022) - Corona, Giovanni; Vena, Walter; Pizzocaro, Alessandro; Vignozzi, Linda; Sforza, Alessandra; Maggi, Mario
Abstract: Background: Type 2 diabetes mellitus and pre‐diabetes are associated with reduced circulating testosterone levels. However, the role of testosterone replacement therapy in these patients is still conflicting. Objectives: To summarize and critically analyze available data on the possible effect of testosterone administration in men with glucose abnormalities. Materials and methods: A comprehensive systematic review was performed. When available, meta‐analytic data were preferred. To better analyze the relationship between testosterone and the pre‐diabetes condition, a systematic analysis was performed and the data obtained with the latter search were used for a meta‐analytic approach. Finally, clinical data derived from a consecutive series of 4682 patients seeking medical care for sexual dysfunction at the University of Florence were also considered. Results: Patients with impaired fasting glucose were characterized by a 3 nmol/L lower level of total testosterone when compared to controls. Similarly, impaired fasting glucose was associated with a 1.8‐fold increased risk of hypogonadism, when compared to subjects with normal glucose levels. Waist circumference and body mass index resulted as being the best predictors of reduced total testosterone levels. Secondary hypogonadism was two times higher in subjects with impaired fasting glucose when compared to rates observed in the general population. Testosterone replacement therapy was able to improve body composition, insulin resistance, and glucose profile both in impaired fasting glucose and type 2 diabetes mellitus whereas its role on body weight, lipid profile, and sexual function was less evident. Discussion and conclusion: Weight loss and physical activities are able to improve both metabolic profile and testosterone levels. The combined approach of testosterone replacement therapy and lifestyle modifications could be suggested in symptomatic hypogonadal men to better motivate patients to perform physical activity which can eventually result in weight loss as well as metabolic profile and sexual function improvement. Whether or not these approaches can prevent the development of type 2 diabetes mellitus from pre‐clinical conditions requires more studies.